DESTE prize (nominated) - Savva, Andreas (My University, 2026)
One of the primary aims of the DESTE Foundation is to support and promote the production of contemporary Greek art, as well as to expand the audience of contemporary art in Greece. To this end, the Foundation decided in 1999 to establish the DESTE Prize, an award that is given biennially to a young, Greek artist for their exemplary work. The Prize intends to encourage and reinforce the spirit of innovation in Greek contemporary art and to highlight its latest developments, bringing the achievements of emerging artists to the attention of a wider public. In selecting the seven finalists, the Selection Committee deemed the following areas to be of particular interest: the relation of national identity (cultural as well as social) to international realities, current issues and the phenomenon of globalization, the examination of contemporary reality in Greece, and the examination of the question of personal identity. The seven short-listed artists for the DESTE Prize 2001 are Christos Athanassiades, Despina Christou, Athanasia Kyriakakos, Dimitra Lazaridou, Eleni Lyra, Georgia Sagri, and Andreas Savva. The Selection Committee also decided that a Special Mention be made to the work of Elias Cohen, who submitted a CD-Rom proposal of interventions for a Metro station – a visually and functionally thorough approach to the question of art in public spaces. An international jury of five will select the winner of this year’s DESTE Prize 2001 and will be announced by the Minister of Culture, Mr. Evangelos Venizelos. The DESTE Prize winner receives 3.000.000 drachmas and is awarded to the artist whose work attempts to open up new ways for art and contributes to the discourse and development of contemporary art in Greece according to the jury’s criteria.
Keywords: Arts and entertainment